Elevated Procalcitonin Level with Primary Hepatic Neuroendocrine Tumor - Aed Abdelqader Banibakr; Mohsin Abdul Rasheed; Sulaiman Al Maqbali; Karim Abdelhakim (Journal of Radiation and Cancer Research, 2025)
Procalcitonin (PCT) is a well-established marker for sepsis, particularly of bacterial origin. In addition, PCT serves as a promising tumor marker for medullary thyroid carcinoma. Elevated levels of PCT have been observed in neuroendocrine tumors (NETs), particularly those originating from the lungs and digestive tract. Although primary hepatic neuroendocrine tumors (PHNETs) are exceedingly rare, there have been a few cases reported in the literature where elevated PCT levels were observed in PHNET patients. This case report discusses a 60-year-old male patient admitted to the hospital with symptomatic hyponatremia, who was found to have significantly elevated PCT levels. The patient underwent an extensive diagnostic workup for potential infectious causes, but no clear source of infection was identified. Despite treatment with a course of empirical broad-spectrum antibiotics, the patient’s PCT levels remained elevated. Radiological investigations revealed hepatic lesions, which were confirmed to be PHNETs upon histopathological examination. This case underscores the potential utility of PCT as a biomarker for NETs, particularly those of hepatic origin.